'Hit and Miss'? Access to Legal Assistance in Immigration Detention. (10th March 2022) - Lindley, Anna
Abstract: In the context of significant cuts to legal aid in the last decade in the UK, immigration detention remains in scope: indeed the argument that detention is legitimate rests partly on the claim that people can challenge it. Drawing on interviews with legal professionals combined with published data and reports, this article concludes that while the publicly funded Detention Duty Advice Scheme delivers advice and representation to many people held in detention, variations in access and quality give grounds for concern. Many people are also forced to rely on private solicitors, pro-bono provision and their own legal capabilities, raising questions regarding effective remedy and equality of access to justice. The article reviews the limited information available on representation types and rates, outcomes, and the wider impact of access to legal representation or the lack of it. The conclusion summarizes key points and explores ways forward.